1998
DOI: 10.1046/j.1523-1739.1998.96349.x
|View full text |Cite
|
Sign up to set email alerts
|

Habitat and Avifaunal Recovery from Livestock Grazing in a Riparian Meadow System of the Northwestern Great Basin

Abstract: Riparian habitats are centers of biological diversity in arid and semiarid portions of western NorthAmerica, but despite widespread loss and degradation of these habitats there is little quantitative information concerning restoration of native riparian biota. We examined the recovery of a riparian meadow system in the context of long-term versus short-term release from livestock grazing. We compared the structure and dynamics of plant and avian communities on 1.5-ha plots inside a long-term ( Ͼ 30 years) live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 20 publications
5
49
0
Order By: Relevance
“…In recent decades great attention have been paid to the population declines of farmland birds attributed to intensive agricultural management (Vickery et al 2001). Grazing generally has negative effect on bird species richness or abundance (Dobkin et al 1998;Fuller and Gough 1999;Verhulst et al 2004;Maron and Lill 2005). In the present study we showed effect of management on species richness and abundance of true grassland birds with higher species richness and abundance on the extensive sites, while on non-grassland species no effect was found.…”
Section: Discussionsupporting
confidence: 48%
“…In recent decades great attention have been paid to the population declines of farmland birds attributed to intensive agricultural management (Vickery et al 2001). Grazing generally has negative effect on bird species richness or abundance (Dobkin et al 1998;Fuller and Gough 1999;Verhulst et al 2004;Maron and Lill 2005). In the present study we showed effect of management on species richness and abundance of true grassland birds with higher species richness and abundance on the extensive sites, while on non-grassland species no effect was found.…”
Section: Discussionsupporting
confidence: 48%
“…reduction in infiltration rates and increased bulk density) (Wheeler et al 2002), water table (e.g. lowering and contraction of the hyporheic zone) (Dobkin et al 1998), stream channels (e.g. enhanced width-depth ratios) (Clary 1999;Scrimgeour and Kendall 2003), stream banks (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…nutrient enrichment) (Agouridis et al 2005). It has been associated with altered community composition and ecological function, and decreased diversity and conservation value for riparian vegetation (Clary 1999;Scott et al 2003), birds (Dobkin et al 1998;Scott et al 2003), aquatic macroinvertebrates (Scrimgeour and Kendall 2003) and small mammals (Giuliano and Homyack 2004). Therefore livestock grazing is likely to have several indirect influences on ERS beetle communities as a result of changes to sediment delivery, vegetation cover, habitat shading, and aquatic food supply (c.f.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to providing important ecological goods and services to human communities, these forests represent important stopover locations for Neotropical land birds that winter in Mexico or migrate between breeding and wintering grounds, which may extend from southern Canada to Central and South America (Skagen et al 1998;Yong et al 1998). In the western US, riparian ecosystems are estimated to occupy between 0.1% and 0.5% of the landscape (Knopf et al 1988;Webb and Leake 2006), yet they typically support a disproportionately large number of bird species and greater densities of birds than other habitats in the continental US (Dobkin et al 1998;Krueper et al 2003). Riparian ecosystems in the US and Canada have received considerable attention from researchers and conservationists (NRC (National Research Council) 2002;Naiman et al 2005).…”
Section: Introductionmentioning
confidence: 99%